STUDENTS' LEARNING ATTITUDES TOWARDS PHYSICS PROBLEM SOLVING ABILITY OF MAN 2 PALU - Muslimin (Universitas Tadulako, 2021)
This study aims to describe the relationship between student learning attitudes and problem-solving abilities in Physics at MAN 2 Palu. This research is qualitative descriptive research. The population is all students of class XI MAN 2 Palu Academic Year 2020/2021 with a sample of 38 students. The instruments used are questionnaire tests in learning physics and essays on physics problem-solving ability tests. The results of the prerequisite test results of the research are that all aspects and indicators of Student Attitudes are normally and linearly distributed and based on the feasibility test indicate that all data are eligible for regression and correlation tests. The results of the analysis of the regression test and the correlation test obtained values ​​that were varied, insignificant, and significant. Based on the results of the research analysis, it can be concluded that the relationship between each indicator of student attitudes towards solving physics problems is four indicators that are not significant and only one indicator of student attitudes is significant. Based on the results of the regression test, correlation, and determination test, it can be concluded: 1. Students' attitudes in learning physics have an effect on physics problem-solving ability but the effect is small. While the attitude in studying physics does not affect the ability to solve physics problems. 2. The relationship between attitudes in learning physics to problem-solving abilities in physics, there is a relationship between aspects of learning physics and problem-solving abilities in physics. While the attitude in studying physics there is no relationship. 3. The contribution of students' learning attitudes to physics problem-solving abilities is 12.96%.